An Exploration of Uncertainty and Waiting in the Short Story “Rencana Satu Kereta Bersama W Mabelle”: A Formalism and Psychological Analysis - Purnomo, Fazrul Sandi; Harista, Eva; Rahmaniyar, Atik (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze the themes of waiting and uncertainty in the short story “Rencana Satu Kereta Bersama W Mabelle” by Aravayana, using a formalist and Freudian psychological approach. The formalist approach identifies intrinsic elements such as structure, plot, symbolism, and style, while the Freudian psychological approach explores the personality aspects of the main character through the concepts of the Id, Ego, and Super-ego. This research is conducted qualitatively by analyzing the text of the short story as the primary object. The results reveal that the themes of waiting and uncertainty are represented through symbols such as the "train" and "unread chat," symbolizing restrained communication and missed opportunities. The non-linear plot and poetic language strengthen the melancholic atmosphere of the story, depicting the main character's feelings trapped in uncertainty. From the perspective of Freudian psychology, the main character experiences a conflict between the Id, which seeks attention from W Mabelle, the Ego, which balances hope and reality, and the Super-ego, which considers the morality of the relationship. This study contributes to understanding contemporary Indonesian literature through an integrative analysis of formalism and psychology, providing a deeper interpretation of the emotional dynamics in literary works. However, this study is limited to intrinsic analysis and the internal conflicts of the main character, suggesting the need for further studies involving socio-cultural context to enrich the understanding of the themes explored.